2007
DOI: 10.1530/eje.1.02335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2 years of high-dose growth hormone therapy on cognitive and psychosocial development in short children born small for gestational age

Abstract: Objective and design: Children born small for gestational age (SGA) are not only at risk for short stature, but also for neurodevelopmental and behavioral problems. In this study, we analyzed the effects of high-dose GH therapy on cognitive development and psychosocial functioning in 34 prepubertal (3-8 years) short SGA children, equally randomized into a GH-treated group (TRG) and an untreated group (UTRG). Methods: At start and after 2 years, children underwent standardized tests measuring the intellectual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…These results are in contrast with the findings in a cohort of SGA children from Belgium. In a randomized controlled trial, no beneficial effect of GH treatment on IQ scores could be observed after 2 years of treatment [6]. A remarkable finding in this study was an increase in IQ scores of about 8 points in untreated SGA children.…”
Section: Gh Therapy and Brain Development Intelligence And Cognitionmentioning
confidence: 58%
See 2 more Smart Citations
“…These results are in contrast with the findings in a cohort of SGA children from Belgium. In a randomized controlled trial, no beneficial effect of GH treatment on IQ scores could be observed after 2 years of treatment [6]. A remarkable finding in this study was an increase in IQ scores of about 8 points in untreated SGA children.…”
Section: Gh Therapy and Brain Development Intelligence And Cognitionmentioning
confidence: 58%
“…There are 2 cohorts of SGA children in which the effect of GH therapy on intelligence and cognition has been evaluated [5,6,83,84]. …”
Section: Gh Therapy and Brain Development Intelligence And Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHTAC excluded the review by Lagrou (2007) as its outcomes did not meet our inclusion criteria. We also excluded the reviews by Bundak (2001) …”
Section: Searches Identified (Studies For Genotropin)mentioning
confidence: 99%
“…In young children born SGA, normalized head circumference was found in the 3-year GH-treated group but not in the untreated group [5], with concomitant positive effects on intelligence and psychosocial functioning [1]. In contrast, IQ in non-GH-deficient SGA children did not improve with GH treatment [6], whereas IQ did improve in children with Prader-Willi syndrome with severe GHD [2]. …”
Section: Introductionmentioning
confidence: 99%